2006
DOI: 10.1080/02640410500497733
|View full text |Cite
|
Sign up to set email alerts
|

Influence of starting position on finishing position in World Cup 500 m short track speed skating

Abstract: Top short track speed skaters and their coaches have suspected that starting positions influence finishing positions, especially in the 500 m racing distance. The objective of this study was to examine systematically the influence of starting position on finishing position in 500 m short track speed skating. The data analysed included results from World Cup 500 m races ranging from the 1999-2000 season through to the end of the 2003-2004 season. All 500 m men's and women's races with four skaters starting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 7 publications
(5 reference statements)
2
19
0
1
Order By: Relevance
“…[14][15][16] Results showed that a starting position closest to the inside of the track (inside lane) was positively correlated with the final-ranking in 500 m short-track competitions, indicating better chances of winning the race when starting in the inside lane. 14,15 The importance of the start-position seemed to decrease in 1000 m and 1500 m short-track races as no correlations were reported here between starting lane and finalranking. 15 These results might be an indication of a more tactical approach to the race when distance increases.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[14][15][16] Results showed that a starting position closest to the inside of the track (inside lane) was positively correlated with the final-ranking in 500 m short-track competitions, indicating better chances of winning the race when starting in the inside lane. 14,15 The importance of the start-position seemed to decrease in 1000 m and 1500 m short-track races as no correlations were reported here between starting lane and finalranking. 15 These results might be an indication of a more tactical approach to the race when distance increases.…”
Section: Introductionmentioning
confidence: 94%
“…14,15 In all 1500 m short-track races the winner was the athlete who first passed the finish line after 13.5 laps, where the distance of a short-track oval is 111.12m.…”
Section: Participants and Eventsmentioning
confidence: 99%
“…While tactics in shorttrack speed skating are quite complex due to the role of competitors [53,54], they are more straight forward in long-track speed skating, a time trial sport. The tactics involved can be mostly identified with pacing: how to distribute available energy over the race to perform maximally.…”
Section: Tactics: Pacing In a Broad Perspectivementioning
confidence: 99%
“…The duration of BMX cycling races have been recorded between 30 s to 50 s (Cowell et al 2012) and therefore the sport is considered predominantly as a sprint type event (Zabala et al 2008). The importance of the start in sprint type events has been reported previously in a number of sports including: speed skating (Maw et al 2006;Muehlbauer 2010;Muehlbauer & Schindler 2011) and 100m, 200m and 110m hurdles in athletics (Pilianidis et al 2012). …”
Section: Introductionmentioning
confidence: 99%